2000
DOI: 10.1073/pnas.240460997
|View full text |Cite
|
Sign up to set email alerts
|

A continuous assay for DNA cleavage: The application of “break lights” to enediynes, iron-dependent agents, and nucleases

Abstract: Although extensive effort has been applied toward understanding the mechanism by which enediynes cleave DNA, a continuous assay for this phenomenon is still lacking. In fact, with the exception of assays for DNase, continuous assays for most DNA cleavage events are unavailable. This article describes the application of ''molecular break lights'' (a single-stranded oligonucleotide that adopts a stemand-loop structure and carries a 5-fluorescent moiety, a 3-nonfluorescent quenching moiety, and an appropriate cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 37 publications
2
79
0
1
Order By: Relevance
“…Supporting online information online includes experimental procedures for the detection of DNA cleavage activity of TLM A, K-1, and K-2 by break-light assay (39) and Tables S1 for plasmids, Tables S2 for bacterial strains, and Table S3 for oligonucleotides as PCR primers used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting online information online includes experimental procedures for the detection of DNA cleavage activity of TLM A, K-1, and K-2 by break-light assay (39) and Tables S1 for plasmids, Tables S2 for bacterial strains, and Table S3 for oligonucleotides as PCR primers used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When the probe undergoes a spontaneous conformational change forcing the stem apart, fluorescence occurs. Recently, molecular beacons have been widely used in the investigation of DNA-protein interactions including DNA cleavage and ligation reactions because of their high sensitivity, simplicity, and real-time monitoring [22][23][24][25] . In this study, we describe a new high-throughput assay that translates the IN 3'-processing reaction into a fluorescent signal in real-time using the principle of molecular beacons.…”
Section: +mentioning
confidence: 99%
“…For example, fluorescence-based assays with "molecular break light" probes and "molecular beacons" were reported for monitoring endonucleases. [16][17][18][19][20][21][22] The use of complexes of DNA and cationic conjugated polymer as probes was recently described. [23] Colorimetric methods based on enzyme-responsive gold nanoparticle (AuNP) [24][25][26][27] and DNAzyme [28] systems have also been developed for detecting endonucleases.…”
Section: Introductionmentioning
confidence: 99%
“…These were at least 100 times more sensitive than those of previously reported methods based on gel electrophoresis and chromatography, UV spectroscopy, and the general fluorescence methods. [16][17][18][19][24][25][26][27][28] These results indicated that the proposed method could be used for quantifying multiple endonucleases simultaneously with high sensitivity and specificity.…”
mentioning
confidence: 99%